2020
DOI: 10.1016/j.cca.2020.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heat-inactivation on the detection of SARS-CoV-2 IgM and IgG antibody by ELISA

Abstract: Background: To establish a safe and accurate method for detecting SARS-CoV-2 IgM and IgG, we assessed the impact of sera after heat-inactivation on the SARS-CoV-2 IgM and IgG levels measured by ELISA-immunoassay. Methods: The serum samples of 62 patients with COVID-19 and 18 healthy controls were collected in Hankou's Hospital of Wuhan from February 27 to March 6, 2020. Before and after the samples were inactivated, the levels of IgM and IgG antibodies were measured. Results: The indexes of antibodies after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 21 publications
0
31
0
2
Order By: Relevance
“… Category Virus Morphology Inactivation Mechanisms Diameter (Average) Genome Type Genome Size UV Light/ozone Chloride/Iodide/Salts Compounds Heat (Temperature Dependent) Acid/Alcohol Other Enveloped Viruses Coronavirus 80-120 nm +ss RNA 26000-32000 bases UV-C 254 (4016 μW/cm 2 ), UV-A 365 (2133 μW/cm 2 ), ϒ (3K-15k rad.) 60 Co ( Glass and O’Brien, 1980 ) Benzalkonium chloride & Laurylamine(RF>3.8, 60 min) ( Kapuscinski and Mitchell, 1980 ) , didecyldimonium chloride(RF>3.8, 60min) ( Kapuscinski and Mitchell, 1980 ) , Hypochlorite(0.1-0.5%, 2-4log 10 ) ( Šim\uunek et al, 2016 ) Heat Treatment (>65 o C) ( Glass and O’Brien, 1980 ) Heat Treatment (60 o C, 30 min) ( Kapuscinski and Mitchell, 1980 ) , Heat on serum(56 o C, 30 min, 90% inactivation,7-14 min) ( Weber and Stilianakis, 2008 ) Sterillium (propanol, ethanol)(RF>4.3, 30 s), (Ethanol, biphenylol) ( Kapuscinski and Mitchell, 1980 ) , Ethanol(80%v/v) (3.8log 10 ) and 2-propanol (75%v/v) (30 S, > 3.8 log 10 ) ( Park et al, 2011 ) Catalytic Oxidation (Ag, 5 min & Cu, 20 min) ( Hu et al, 2020 ), Formaldehyde ( Glass and O’Brien, 1980 ) & Glutaraldehyde ( Glass and O’Brien, 1980 ), ( Kapuscinski and Mitchell, 1980 ), Incidin Plus, Wine Vinegar( Šim\uunek et al, 2016 ), Glutardi...…”
Section: Transport Of Virusesmentioning
confidence: 99%
“… Category Virus Morphology Inactivation Mechanisms Diameter (Average) Genome Type Genome Size UV Light/ozone Chloride/Iodide/Salts Compounds Heat (Temperature Dependent) Acid/Alcohol Other Enveloped Viruses Coronavirus 80-120 nm +ss RNA 26000-32000 bases UV-C 254 (4016 μW/cm 2 ), UV-A 365 (2133 μW/cm 2 ), ϒ (3K-15k rad.) 60 Co ( Glass and O’Brien, 1980 ) Benzalkonium chloride & Laurylamine(RF>3.8, 60 min) ( Kapuscinski and Mitchell, 1980 ) , didecyldimonium chloride(RF>3.8, 60min) ( Kapuscinski and Mitchell, 1980 ) , Hypochlorite(0.1-0.5%, 2-4log 10 ) ( Šim\uunek et al, 2016 ) Heat Treatment (>65 o C) ( Glass and O’Brien, 1980 ) Heat Treatment (60 o C, 30 min) ( Kapuscinski and Mitchell, 1980 ) , Heat on serum(56 o C, 30 min, 90% inactivation,7-14 min) ( Weber and Stilianakis, 2008 ) Sterillium (propanol, ethanol)(RF>4.3, 30 s), (Ethanol, biphenylol) ( Kapuscinski and Mitchell, 1980 ) , Ethanol(80%v/v) (3.8log 10 ) and 2-propanol (75%v/v) (30 S, > 3.8 log 10 ) ( Park et al, 2011 ) Catalytic Oxidation (Ag, 5 min & Cu, 20 min) ( Hu et al, 2020 ), Formaldehyde ( Glass and O’Brien, 1980 ) & Glutaraldehyde ( Glass and O’Brien, 1980 ), ( Kapuscinski and Mitchell, 1980 ), Incidin Plus, Wine Vinegar( Šim\uunek et al, 2016 ), Glutardi...…”
Section: Transport Of Virusesmentioning
confidence: 99%
“…at 56˚C has been suggested to reduce virus infectivity and exposure concerns and can minimize background through inactivation of the complement system, but can also yield denaturation and aggregation of IgG and IgM thus interfering with serological detection [ [86] , [87] , [88] ]. The limited available information to date indicates mixed results on the subsequent impact of heat inactivation on immunological detection for SARS-CoV-2, indicating increased false negatives in an IgM immunochromatographic assay and no significant impact on an ELISA for detection of IgG and IgM [ 89 , 90 ]. Dried blood spot collections provide an opportunity for greater access to testing through easier sample collection and submission, though have similarly had mixed results with one study showing a 30-fold higher limit of detection using dried blood spots than for plasma but another showing comparable results [ 91 , 92 ].…”
Section: Challenges With Serology Assay Development and Implementatiomentioning
confidence: 99%
“…Previous other virus studies suggest that serum heat inactivation and optimal dilution enhance WNV E-MIA sensitivity by eliminating the complement interference, thereby detecting low-titer anti-WNV antibodies during early and late phases of infection ( Namekar et al, 2012 ). Recently, two groups have reported that heat-inactivation of blood samples at 56 ℃ for 30 min does not obviously affect the results of immunochromatography and chemiluminescent immunoassay for detection of SARS-COV-2 antibodies ( Xue et al, 2020 ; Hu et al, 2020 ). However, heat-inactivation cannot be used in fluorescence immunochromatography for SARS-CoV-2 antibody detection because negative samples became positive after heat-inactivation ( Xue et al, 2020 ), which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%